Brain Imaging Studies on the Cognitive, Pharmacological and Neurobiological Effects of Cannabis in Humans: Evidence from Studies of Adult Users - Weinstein, Aviv; Livny, Abigail; Weizman, Abraham (Current Pharmaceutical Design, 2016)
Cannabis is the most widely used illicit drug worldwide. Regular cannabis use has been associated with a range of acute and chronic mental health problems, such as anxiety, depression, psychotic symptoms and neurocognitive impairments and their neural mechanisms need to be examined. This review summarizes and critically evaluates brain-imaging studies of cannabis in recreational and regular cannabis users between January 2000 and January 2016. The search has yielded eligible 103 structural and functional studies. Regular use of cannabis results in volumetric, gray matter and white matter structural changes in the brain, in particular in the hippocampus and the amygdala. Regular use of cannabis affects cognitive processes such as attention, memory, inhibitory control, decision-making, emotional processing, social cognition and their associated brain areas. There is evidence that regular cannabis use leads to altered neural function during attention and working memory and that recruitment of activity in additional brain regions can compensate for it. Similar to other drugs of abuse, cannabis cues activated areas in the reward pathway. Pharmacological studies showed a modest increase in human striatal dopamine transmission after administration of THC in healthy volunteers. Regular cannabis use resulted in reduced dopamine transporter occupancy and reduced dopamine synthesis but not in reduced striatal D2/D3 receptor occupancy compared with healthy control participants. Studies also showed different effects of Δ-9 tetrahydrocannabinol (THC) and cannabidiol (CBD) on emotion, cognition and associated brain regions in healthy volunteers, whereby CBD protects against the psychoactive effects of THC. Brain imaging studies using selective high-affinity radioligands for the imaging of cannabinoid CB1 receptor availability in Positron Emission Tomography (PET) showed downregulation of CB1 in regular users of cannabis. In conclusion, regular use of the cannabinoids exerts structural and functional changes in the human brain. These changes have profound implications for our understanding of the neuropharmacology of cannabis and its effects on cognition, mental health and the brain.
Keywords: cannabidiol